(3GdTGaj aj TQM eSfO GdTGaYis - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s; (3CHh YHO Gddg eMeO Hf EOQjS Hf GdYHGS Hf YKeGf Hf TGaY (B( (3GdEeGe GdTGaYj (B)(3,J (B204 (3g` s
(3ChdgG (B:s
(3jHJOF HEeGeI GdCYei s
(3BNQgG (B:s
(3hjfJgi HRjGQI GdbHhQ s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B32s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B83 s
Keywords: (3GdMOjK h GdeUWdMs